Do characteristics of audit committees and board of directors influence earnings management?. (1st January 2014) - Pathak, Jagdish; Karim, Khondkar E.; Suh, SangHyun; Zhang, Ziwen
Earnings management has attracted much attention in this globalised economic environment due to large accounting scandals such as Enron and WorldCom. National governments and other market-regulation institutions are taking measures to restrain earnings management in order to ensure the reliability and transparency of financial reporting. This study explores whether audit committees and boards of directors influence earnings management using the literary review method. The findings show that both discretionary accruals and abnormal accruals are mostly used as dependent variables to detect earnings manipulation estimated by the Jones and modified Jones models. For the most part, evidence from previous literature indicates that the more independent the members of the audit committee and board, the higher the quality of earnings in financial reporting. However, some opposite findings exist.